Effect of N, P and K fertilization in the production of aerial biomass of cuttings of Festuca dolichophylla (Presl, 1830) and Festuca humilior (Nees & Meyen, 1841) - Trillo Zárate, Fritz Carlos (2020)
The aim of this study was to compare the effect of N, P and K fertilization on the production of aerial biomass of two native grasses Festuca dolichophylla and Festuca humilior. The experiment was carried out in the SAIS Túpac Amaru, Junín, Peru, at an altitude of 4186 m. The treatments were N, P, K, NPK and a control. The nitrogen, phosphorus and potassium doses were 36.24, 4.27 and 29.92 kg/ha, respectively. The model of blocks with orthogonal contrasts was used. The variables were: fresh aerial biomass (kg/ha), dry aerial biomass (kg/ha) and percentage of dry matter. Fresh aerial biomass was 783.9±110.7 and 662.9±24.9 kg/ha, dry aerial biomass was 477.6±62.9 and 410.2±15.4 kg/ha, and percentage of dry matter was 64.11±1.82 and 61.47±0.56% in F. dolichophylla and F. humilior, respectively, with F. dolichophylla being the species with the highest production of aerial biomass (p<0.05). Fresh aerial biomass was 828.6±54.8 and 604.9±61.9 kg/ha, and dry area biomass was 502.7±32.7 and 373.7±37.4 kg/ha in the plots with and without fertilization of F. dolichophylla, respectively (p<0.05), and without significant differences for the percentage of dry matter. F. dolichophylla showed a stimulus to the fertilization of N, P and K, improving biomass production due to the immediate availability of some macronutrient. The percentage of dry matter in F. dolichophylla and F. humilior did not show a higher nutrient retention in the shrub. The limiting element could not be identified for these species, probably due to compensatory responses to nutritional deficit.